Imaging genetics - Dalca, Adrian V. (Adrian Vasile); Batmanghelich, Nematollah K. (Nematollah Kayhan); Sabuncu, Mert Rory, 1979-; Shen, Li (Radiologist) (Elsevier and MICCAI Society book series., 2018)
"Imaging Genetics presents the latest research in imaging genetics methodology for discovering new associations between imaging and genetic variables, providing an overview of the state-of the-art in the field. Edited and written by leading researchers, this book is a beneficial reference for students and researchers, both new and experienced, in this growing area. The field of imaging genetics studies the relationships between DNA variation and measurements derived from anatomical or functional imaging data, often in the context of a disorder. While traditional genetic analyses rely on classical phenotypes like clinical symptoms, imaging genetics can offer richer insights into underlying, complex biological mechanisms. Contains an introduction describing how the field has evolved to the present, together with perspectives on its future direction and challenges Describes novel application domains and analytic methods that represent the state-of-the-art in the burgeoning field of imaging geneticsIntroduces a novel, large-scale analytic framework that involves multi-site, image-wide, genome-wide associations"--